Characterization of Tigecycline-Heteroresistant Klebsiella pneumoniae Clinical Isolates From a Chinese Tertiary Care Teaching Hospital - Zhang, Qiaoyu; Lin, Liping; Pan, Yuhong; Chen, Jiansen (Frontiers in Microbiology, 2021)
Tigecycline has been used as one of the therapeutic choices for the treatment of infections caused by multidrug-resistant K. pneumoniae. However, the emergence of tigecycline heteroresistance has brought a great challenge in the treatment. The purpose of this study was to investigate whether tigecycline heteroresistant K. pneumoniae (TGCHR-Kp) exists in clinical isolates, and further to characterize the underlying molecular mechanisms involved in development of tigecycline resistant subpopulations. Of the 268 tigecycline-susceptible clinical K. pneumoniae isolates, 69 isolates were selected as tigecycline heteroresistant candidates in the preliminary heteroresistant phenotyps selection by a modified disk diffusion method, only 21 strains were confirmed as TGCHR-Kp by the population analysis profile (PAP). Pulsed Field Gel Electrophoresis (PFGE) analysis demonstrated that all the parental TGCHR-Kp isolates were clonally unrelated, and colonies confirmed as the heteroresistant subpopulation showed no significant differences to their respective parental TGCHR-Kp isolate. Efflux pump inhibitors reversed the tigecycline susceptibility in heteroresistant strains. It is mainly related to the mutations of ramR, soxR genes, lead to upregulation of ramA and soxS transcriptional regulators, which in turn induce overexpression of efflux pump AcrAB-TolC efflux pump genes in TGCHR-Kps resistant subpopulations. Moreover, mutations of rpsJ were also found in resistant subpopulations, which suggested that rpsJ mutation may also lead to tigecycline resistance. Time-kill assay showed the efficacy of tigecycline against TGCHR-Kps was weakened, whereas the number of resistant subpopulations were enriched by the presence of tigecycline. Our findings imply that the presence of TGCHR-Kps in clinical strains is a severe challenge to tigecycline therapy in clinical practice.